General Interest - Acosta Gallo, Pablo (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The concept of general interest is firmly implanted in our Constitution and in our legal texts. The clause "general interests" legitimizes the action of government and the very existence of the State as well as its powers to limit the spheres of freedom of citizens. However, our legal system does not offer a definition of what general interests are. In this study we try to find the characteristics that allow us to orient the administrative action towards the satisfaction of the general interests as well as to identify the elements that construct the concept.
Keywords: General interest; general interests; public utility; social interest; public service